The master builder : how the new science of the cell is rewriting the story of life - Martinez Arias, Alfonso, 1955- (Basic Books, Hachette Book Group, 2023)
"What defines who we are? For decades, the biological answer has been our genes. In The Master Builder, leading biologist Alfonso Martinez Arias breaks with decades of scientific and popular tradition to make a bold argument: what defines us is our cells. Drawing on new research from his lab and others, Martinez Arias reveals that we are composed of a thrillingly complex, constantly rearranging symphony of cells that know how to count, feel, and ultimately give form to our bodies. While DNA is important, Richard Dawkins's vision of the selfish gene that controls everything is not a good description of how biology actually works. As Martinez Arias shows, nothing in your genes explains why your heart is on the left side of your body, why you have five fingers and not ten, or why genetically identical twins have different sets of fingerprints and why it's possible for a mother to apparently share no DNA with the children to whom she gave birth! At the heart of it all is not simply gee-whiz science, but a powerful new conception of the essence of life. Our identities are shaped not simply by our genes, but by the interconnections between all our cells, working as a sort of symphony -- cooperative, and creating something greater than its parts could on their own -- and the unbroken lineage of cells that connects us to the first fertilized egg from which we developed -- and in turn, back through the billions of years of our planet's history, to the very first cell in the history of all life on Earth"--